Glorifying War in Iraqi Children's Short Stories 1980s - Kheirbek, Taymaa H (Majallat Jāmiʻat Kūyah lil-ʻulūm al-insānīyah wa-al-ijtimāʻīyah, 2021)
Throughout history, literature has always played a key role in forming societies' cultural heritage. Children Literature, in specific, is highly important since it helps the young readers to develop love and passion for reading which will eventually improve their emotional intelligence and creativity. It also nurtures significant social skills that enable the readers to have more positive attitudes about their lives. Nevertheless, children's literature can turn into a tool to control children and brainwash them. Studying Iraqi children's short stories during the 1980s shows how children are enculturated and treated as rich soil to sow the seeds of violence. In this paper, a selected number of short stories that were written during Iran-Iraq war are studied. It examines how these texts are engaged in literature of propaganda. It also focuses on the tools that are used to covey certain ideologies. The normalization, historicization, and mythologization of war are proved to be highly influential methods. Propagandistic and militaristic subjects and illustrations are also employed to convey implied ideological messages. The soldiers' suffering is hidden while their death is celebrated. Instead of portraying the ferocity of war to remind young readers of its inhumane side, violence is encouraged, and the idea of peace is trivialized and rejected.